AGROINDUSTRI TEH DAUN GAHARU DI KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN PEKANBARU (STUDI KASUS CV. GAHARU PLAZA INDONESIA) - Chandra Leonardo; Fahrial (DINAMIKA PERTANIAN, 2020)
ABSTRACT Agarwood leaf Aquilaria malaccensis Lamk is used as a raw material in the agroindustry of agarwood leaf tea. This study aimed to analyze the production cost, revenue, profit, efficiency, and value-added. This research used a survey method as a case study of the CV. Gaharu Plaza Indonesia which was conducted in Sidomulyo Barat Village, Tampan District, Pekanbaru. The results of the study showed that the agarwood leaf tea agroindustry by CV. Gaharu Plaza Indonesia is a small business or micro business. The technology in processing agarwood leaf tea is semi-mechanical and has a home industry food production certificate, a small trade business permit, and the health department. The raw material used for the one-time production process for the agro-industry of agarwood leaf tea was as much as 4 kg of agarwood leaves, with supporting materials such as jasmine flowers, tea bags, packaging boxes, standing pouch packaging, transparent roll plastic, and packaging labels. Production cost was IDR 1.715.894, the income of IDR 4.250.000, net profit of IDR 2.534.106, the added value of processing aloes into aloes leaf tea was IDR 13.269. The RCR value was 2,48 with the criteria RCR value > 1 is profitable and feasible to be developed. Keywords: Agroindustry, Agarwood leaf tea, Value added